Linking citizens and parties how electoral systems matter for political representation - Ezrow, Lawrence; European Consortium for Political Research (Oxford : Oxford University Press, 2010)
This text addresses familiar questions about political representation. These fundamental questions are paired with the empirical observation of Western European democracies during the last 30 years. The study highlights the pathways through which citizens' political preferences are expressed by their political parties.
At foot of title: "ECPR".
Description based on print version record.
Includes bibliographical references and index.
Keywords: Democracy; Political parties; Political participation; Voting